2010
DOI: 10.1038/labinvest.2009.104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric oxide synthesis during induced cholestasis ameliorates hepatocellular injury by facilitating S-nitrosothiol homeostasis

Abstract: Cholestatic liver injury following extra-or intrahepatic bile duct obstruction causes nonparenchymal cell proliferation and matrix deposition leading to end-stage liver disease and cirrhosis. In cholestatic conditions, nitric oxide (NO) is mainly produced by a hepatocyte-inducible NO synthase (iNOS) as a result of enhanced inflow of endotoxins to the liver and also by accumulation of bile salts in hepatocytes and subsequent hepatocellular injury. This study was aimed to investigate the role of NO and S-nitroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…We have previously shown that NOS-2 overexpression in the BDL group is associated with the hepatocellular injury [15]. According to the results of the present study, the adverse effects exerted by NO during cholestatic injury might be due to both the increase in NOS-2 and the reduction in NOS-3 expression.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We have previously shown that NOS-2 overexpression in the BDL group is associated with the hepatocellular injury [15]. According to the results of the present study, the adverse effects exerted by NO during cholestatic injury might be due to both the increase in NOS-2 and the reduction in NOS-3 expression.…”
Section: Discussionsupporting
confidence: 80%
“…This result is not surprising since the hepatic cholestasis was associated with tissue fibrosis [15], and liver fibrosis has been previously linked to changes in the expression of commonly used loading control proteins [42,43]. We have previously shown that NOS-2 overexpression in the BDL group is associated with the hepatocellular injury [15].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The excessive generation of NO has been observed both in experimental cholestasis [34,35] and in primary biliary cirrhosis patients [36,37]. Renal impairment occurs in cirrhotic patients with a high concentration of NO in the plasma and ascitic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that overall Snitrosylation levels increase in NO donor-treated hepatic stellate cells (29). Recent work has shown that inhibition of nitric oxide synthesis during induced cholestasis can ameliorate hepatocellular injury by facilitating S-nitrosothiol homeostasis (23). Despite these findings, very little work has been done investigating a role for S-nitrosylation in the regulation of hepatic transporters.…”
mentioning
confidence: 99%